The Oyashio Nutrient Stream and Its Nutrient Transport to the Mixed Water Region - Yu Long; Xiao‐Hua Zhu; Xinyu Guo (Geophysical Research Letters)
Abstract The Oyashio, a subarctic western boundary current in the North Pacific, transports cool, fresh, and nutrient‐rich water equatorward. The Oyashio nutrient stream was assessed using long‐term mean hydrographic observation data. Its nitrate transport (about 350 kmol/s) is comparable to that of the Kuroshio but has a much shallower subsurface core at 250‐m depth. In the layer ranging from 26.6 to 27.4 σθ, the Oyashio nitrate transport to the mixed water region is about 110 kmol/s. This corresponds to the nitrate transport of the Oyashio to the North Pacific Intermediate Water in the mixed water region. Along with this process, the subarctic gyre nitrate export to the subtropic gyre reaches 24 kmol/s. This work first quantifies the Oyashio nutrient transport and its intrusion into the mixed water region and suggests its importance in local/basin‐scale nutrient cycles.